Binder-free activated graphene compact films for all-solid-state micro-supercapacitors with high areal and volumetric capacitances - Wu, Zhong Shuai; Yang, Sheng; Zhang, Lili; Wagner, Jakob B.; Feng, Xinliang; Müllen, Klaus (Energy Storage Materials, 2015)
Micro-supercapacitors (MSCs) hold great promise as highly competitive miniaturized power sources satisfying the increased demand in microelectronics; however, simultaneously achieving high areal and volumetric capacitances is still a great challenge. Here we demonstrated the designed construction of binder-free, electrically conductive, nanoporous activated graphene (AG) compact films for high-performance MSCs. The binder-free AG films are fabricated by alternating deposition of electrochemically exfoliated graphene (EG) and nanoporous AG with a high specific surface area of 2920 m2/g, and then dry transferring onto the target substrates with a high-pressure mechanical densification process. Remarkably, the resulting compressed AG films showed uniform morphology in lateral dimensions, high conductivity (60 S/cm), nanoporous feature (<10 nm), and high packing density (0.8 g/cm3). The all-solid-state MSCs (AG-MSCs) based on these AG films simultaneously delivered an unprecedented areal capacitance of 89.5 mF/cm2 and volumetric capacitance of 147 F/cm3 for MSCs at 10 mV/s. Moreover, the fabricated AG-MSCs could be operated at a large scan rate of 10,000 mV/s, and showed outstanding cycling stability (capacitance retention of >99.6% after 10,000 cycles). Our results suggested that AG-MSCs are competitive for prospective applications of miniaturized energy storage devices.
CRIS-Team Scopus Importer:2023-03-20